La presse pour enfants au XIXe siècle en Espagne : un objet d’étude fécond et prometteur - Aliénor Asselot (Cahiers de Civilisation Espagnole Contemporaine)
After a first publication at the end of the 18th century, the periodical press for children begins to take shape in Spain in the 1840s, reaching more than seventy titles published by the end of the century. Often described as conservative because of its austerity and the density of its texts, it suffers in the historiography from comparisons with the press of the following century and with the editorial paths of neighbouring nations. Nevertheless, it is in many ways a valuable source for cultural history, since it reveals the gradual demarcation of childhood as a specific editorial market and a specific public. The children’s periodical press is also part of a wider literary and intellectual world, which must be taken into account. Finally, through its socially situated position, it offers a fascinating receptacle of representations and mentalities, where a shared class identity is beginning to emerge, within texts and images.